Флора середнього басейну Росі як джерело для інтродукції гідрофільних видів рослин - Sobko, V.G.; Babenko, L.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The aquatic and riverside flora of the Ros river has been studied. The systematic and geographical structure of the flora it was analyzed in order to make prediction of the progress of hydrophilic plants introduction in the artificially transformed pools of the dendrological park “Alexandria”. Special attention is given to the hydrophilic species as those valuable for the national economy and science, as well as to the species to be preserved and those entered in the Red Book of Ukraine and the European Red List.